REPRESENTASI BUDAYA NUSANTARA DALAM ANIMASI BINEKON - Rinkapati Swatriani (Narada : Jurnal Desain dan Seni, 2020)
The characters contained in the Binekon animation are "representatives" of the culture that exists in Indonesia. Similar to a film, animation also has elements of construction and social representation that want to be built by giving meaning in the reality that occurs in society. Researchers will focus on discussing how the portrayal of binekon animated characters is represented from the social reality of the ethnic / racial communities of the Archipelago with the Pierce semiotic method. The triadic sign model proposed by Pierce, is depicted simply with three points, namely the sign, object, and interpreter. The hallmarks of this study are the characters found in the animations, with the visuals present in each character, then the intepretant is the archipelago culture. And the results of the study showed every character contained in the Binekon animation by Belantara Studio is a cultural representation of the archipelago that represents the major islands in Indonesia, namely Sumi from Sumatra, Jabo from Java, Kale from Kalimantan Island, Sula from Sulawesi Island, and Papu from Papua Island.